2022
DOI: 10.1177/09612033221097812
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of telitacicept in refractory childhood-onset systemic lupus erythematosus: A self-controlled before–after trial

Abstract: Objective To observe the efficacy and safety of telitacicept in refractory childhood-onset systemic lupus erythematosus (cSLE). Methods A self-controlled before–after trial. Children with active SLE, aged 5–18 years, who cannot tolerate side effects of glucocorticoid, were enrolled in our study. Patients received subcutaneous injection of telitacicept weekly based on the standard treatment. SLE responder index-4 (SRI-4) was assessed before the first administration and at least 4 weeks after the first administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 26 publications
3
13
1
Order By: Relevance
“…Additionally, we observed lower levels of immunoglobulin (Ig) G, IgM and IgA compared to baselines, similar to previous studies, 1 indicating that a low dose of telitacicept might also inhibit the abnormal activity of B lymphocytes. Anti-double-stranded DNA antibody was slightly higher than the normal level at follow-up, and the low levels of C3 and C4 complement in the patient did not significantly increase, as reported in previous clinical trials, 6 which might be related to the lower dosing strategy. No adverse events were observed during the treatment.…”
Section: O R R E S P O N D E N C E Safety Efficacy and Pharmacokineti...supporting
confidence: 73%
See 2 more Smart Citations
“…Additionally, we observed lower levels of immunoglobulin (Ig) G, IgM and IgA compared to baselines, similar to previous studies, 1 indicating that a low dose of telitacicept might also inhibit the abnormal activity of B lymphocytes. Anti-double-stranded DNA antibody was slightly higher than the normal level at follow-up, and the low levels of C3 and C4 complement in the patient did not significantly increase, as reported in previous clinical trials, 6 which might be related to the lower dosing strategy. No adverse events were observed during the treatment.…”
Section: O R R E S P O N D E N C E Safety Efficacy and Pharmacokineti...supporting
confidence: 73%
“…11 Due to its promising efficacies, telitacicept, the dual inhibitor of BLyS and APRIL, received final approval from the State Food and Drug Administration of China on March 12, 2021, becoming the first "double-target" class-I novel biological agent for SLE treatment worldwide. 6 In this study, based on the findings low-dose telitacicept in our reported patient, we believe it might be used as a promising approach to treat elderly patients with SLE and LN. Despite the innovative and practical findings described in this study, there were some limitations worth mentioning.…”
Section: O R R E S P O N D E N C E Safety Efficacy and Pharmacokineti...mentioning
confidence: 72%
See 1 more Smart Citation
“…The urinary protein level in 2 of the 8 cases was negative, and the plasma albumin level in 5 of the 8 cases increased to normal. In addition, 3 of these 8 cases demonstrated varying degrees of improvement in renal impairment, with increases in estimated glomerular filtration rate (eGFR, mL/min/1.73 m 2 ) from 17.4 to 26.6, 40.7 to 48.2, and 63.2 to 146.0 12 …”
Section: Discussionmentioning
confidence: 99%
“…A phase III trial of atacicept is being conducted in LN (Table 2). Another dual BAFF and APRIL inhibitor, telitacicept, resulted in a SRI-4 response in 10 out of 15 patients with refractory childhood-onset SLE in an observational cohort study [28] which was followed by phase III trials in SLE (Table 1). Ianalumab (VAY736) is a fully humanized monoclonal antibody against the BAFF receptor.…”
Section: Introductionmentioning
confidence: 99%